A Comparative Study of Prevalence of RTI/STI Symptoms and Treatment Seeking Behaviour among the Married Women in Urban and Rural Areas of Delhi - Verma, Anjana (Int J Reprod Med, 2015)
Background. In developing countries, women are at high risk for several reproductive health problems especially RTI/STIs. Since all RTIs/ STIs are preventable and most of them are curable, it is pertinent to study the determinants of the health seeking behaviour. Objectives. To compare the prevalence and treatment seeking behaviour about RTI/STI symptoms among the married women of reproductive age group (18–45 years) living in urban and rural area of Delhi. Methods. A cross-sectional study was done among the married women of reproductive age group residing in Pooth Khurd, a village in North West district of Delhi, and Delhi Gate, an urban locality situated in central Delhi. Results. In this study, the prevalence of RTI/STI symptoms was found to be similar in both urban (42.3%) and rural area (42%). In urban area, 73% sought treatment, while in rural area only 45.6% sought treatment. Prevalence of the symptoms was found to be higher among the study subjects who were not using any contraceptive method, had history of abortion, and were with lower educational status, in both urban and rural areas. Treatment seeking behaviour was significantly higher among the educated women, contraceptive users, and older age group women in both rural and urban area.